Averaged capture cross sections and radiative strength functions in pf-shell nuclei - Nemashkalo, B.A.; Storizhko, V.E. (Вопросы атомной науки и техники, 2003)
The paper presents experimental results from proton capture reactions by nuclei ⁴⁵Sc, ⁴⁸,⁵⁰Ti, ⁶⁰,⁶¹,⁶²,⁶⁴Ni, ⁶³,⁶⁵Cu, ⁵⁶,⁵⁸Fe, ⁶⁶,⁶⁸Zn, ⁶⁹Ga, ⁷²,⁷⁴Ge, and ⁷⁶,⁷⁸Br, namely, partial cross sections and radiative strength functions (RSF) simulated in the framework of a statistical model and new phenomenological approaches to the description of the RSF developed by Kadmensky, Sirotkin, and Plujko. Data for the reactions ⁶³,⁶⁵Cu(р,g) ⁶⁴,⁶⁶Zn are original. The measurements were performed in NSC KIPT using a Van de Graaf accelerator for 4.5 MeV. The RSFs were determined so as to achieve the best agreement between the measured and the calculated cross sections for fixed global parameters of the statistical model. The measured RSF values are model-dependent. As was found, the RSF is influenced by the excitation energy and final state properties of nuclei, contrary to Brink’s hypothesis that denies the relationship between the RSF and the nuclear structure. These results can be extended to all pf-shell nuclei. Представлено результати експериментальних досліджень реакції захоплення протонів ядрами ⁴⁵Sc, ⁴⁸,⁵⁰Ti, ⁶⁰,⁶¹,⁶²,⁶⁴Ni, ⁶³,⁶⁵Cu, ⁵⁶,⁵⁸Fe, ⁶⁶,⁶⁸Zn, ⁶⁹Ga, ⁷²,⁷⁴Ge, and ⁷⁶,⁷⁸Br-парціальні перерізи і радіаційні силові функції (РСФ),та їх моделювання в рамках статистичної теорії і нових феноменологічних підходів, які були развинуті в роботах Кадменського, Сироткіна, Плюйко. Дані для реакцій ⁶³,⁶⁵Cu(р,g) ⁶⁴,⁶⁶Zn оригінальні. Вимірювання проводились на мішенях товщиною ~1...2 мкм в інтервалі енергій протонів від 1,3 до 3,2 МеВ. РСФ визначені як такі, що дозволяють описати спостережені перерізи захоплення при фіксованих (глобальних) параметрах статистичної моделі. Отримані таким чином РСФ є модельно залежними. Спостерігається залежність силових функцій від характеристик кінцевих станів ядер, а також від енергії збудження, що є прямим порушенням гіпотези Брінка. Наслідки можуть бути розповсюджені на всі ядра pf-оболонки. Представлены результаты экспериментальных исследований реакции захвата протонов ядрами ⁴⁵Sc, ⁴⁸,⁵⁰Ti, ⁶⁰,⁶¹,⁶²,⁶⁴Ni, ⁶³,⁶⁵Cu, ⁵⁶,⁵⁸Fe, ⁶⁶,⁶⁸Zn, ⁶⁹Ga, ⁷²,⁷⁴Ge, and ⁷⁶,⁷⁸Br -парциальные сечения и радиационные силовые функции (РСФ), и их моделирование в рамках статистической теории и новых феноменологических подходов, развитых в работах Кадменского, Сироткина, Плюйко. Данные для реакции ⁶³,⁶⁵Cu(р,g) ⁶⁴,⁶⁶Zn являются оригинальными. Измерения проводились на мишенях толщиной ~1...2 мкм в интервале энергий протонов от 1,3 до 3,2 МэВ. РСФ определены как такие, которые позволяют описать наблюдаемые сечения захвата при фиксированных (глобальных) параметрах статистической модели. Полученные РСФ являются модельно зависимыми. Наблюдается зависимость силовых функций от свойств конечных состояний ядер, а также от энергии возбуждения, что является прямым нарушением гипотезы Бринка. Выводы могут быть распространены на все ядра pf-оболочки.